GEOGRAPHY LEARNING MEDIA BASED ON CHARACTER EDUCATION IN THE DIGITAL REVOLUTION ERA - Ayu Suciani; Desy Irafadillah Effendi; Evi Zulida; Soedirman Z (Universitas Negeri Medan, 2021)
The world is facing the era of industrial revolution 4.0, where everything is connected to machines. In realizing human resources that are ready for the era of the industrial revolution 4.0, the government makes several efforts through education. Character is one of the cornerstones of the progress of a nation. Character is not inherited from birth but needs to be nurtured to grow into the nation's character. The character can be formed through school education in geography subjects. Learning geography will introduce students to the area where they are located. Thus, geography can develop religious, nationalist, independent, cooperative, and integrity characters who love the homeland. This study aims to determine the character of students in the development of character-based learning media. This research was conducted at the Geography MGMP of SMA in Langsa City and East Aceh Regency, totaling 27 teachers. Data collection techniques are interviews and information on the types of learning media on geography material in high School and the characters needed to study geography. The research results are (1) Teachers choose 83% of high school geography materials that require video as a learning medium. Videos are considered capable of providing explanations in the form of images with movement and sound. Thus, videos can help students understand geography material; (2) Interactive multimedia is a suitable medium to foster independent character in students. This media is interactive where the media will present material or information according to what students want; therefore, teachers must develop interactive multimedia for their students; (3) Teachers have the same difficulty in developing geography learning media. The difficulty is the lack of skills in the use of IT technology.Keywords: Learning Media, Character Education, Geography Education, Digital Revolution